Beyond Remembering the Forgotten Parent: The Conception of the Father. Issue 1 (2nd January 2021) - Berman, Sarah
Abstract: While it is true that the father occupies the third position and that he is excluded from the mother-infant dyad, he does not have to be the "forgotten" parent, and, in the last few decades, there has been an increased interest in remembering the father. However, in both theory and practice, the focus seems to be on remembering the importance of the father for the mother and infant, while comparatively little attention has been given to the father himself. In particular, there is a lack of research on the father's representation of himself as a father. In an effort to explore the representational world of the father, psychoanalytic research interviews were conducted with South African fathers whose infants were in the phase of pre-oedipal development. The findings suggest that, for the fathers in this research study, rudimentary and inchoate representations of the self as a father predominate until the father experiences his infant as actively responsive to him. At this point, the father appears to undergo a highly affective, internal reconstitution which binds him to his infant and which begins to enrich his representation of himself as a father. Through the mirroring gaze of the infant, the father is conceived.